PENGARUH NEED FOR COGNITION DAN TAKTIK PENJUALAN TERHADAP PERSEPSI HASIL TAWAR MENAWAR - Asnan Furinto (Universitas Trisakti, 2008)
Many consumer purchase contexts are carried out in environments without clear reference points against which consumers assess their relative satisfaction on the bargaining outcome. In the absence of a reference point, perceptions of bargaining outcome may be influenced by cues which are made salient during the course of a bargaining process, one of those is the seller's response time to the proposal offered by a prospective buyer. Through the mediating role of perceived level of conflicts, response time affects the perceived level of bargaining result. Following up1n*e><evious work of Srivastava and Oza (2006) on the effect of seller's response time on buyer's bargaining outcome perception, the author proposes 2 (two) new constructs which take into account the characteristics attributed to the buyer and seller respectively.In order to be able to qualify seller's response time as a valid cue for consumers to assess the seller's internal conflict, author argues that consumers might need to possess sufficient need for cognition (NFC). Consumers with high NFC will put less dependency on response time as a valid clue to infer the level of opponent's conflict in a bargaining process, compared to consumers with low NFC. Borrowing from the literature of adaptive selling behavior, author further argues that the selling style of a seller could also play a moderating role affecting the relationship between seller's level of conflict and buyer's perception on the bargaining outcome. Sellers using internalization selling tactics may reduce the effect of conflict on perceived bargaining outome, while the use of identification selling tactics may give moderating effects in the opposite direction. Future empirical research to test the proposed relationships among variables is strongly encouraged.Keywords: Consumer purchase, Bargaining process, Perspective buyer